2001
DOI: 10.1116/1.1408949
|View full text |Cite
|
Sign up to set email alerts
|

High speed, dry etching of Fe for integration of magnetic devices in microelectronics

Abstract: Articles you may be interested inA high-speed magnetic tweezer beyond 10,000 frames per second Rev. Sci. Instrum. 84, 044301 (2013); 10.1063/1.4802678 High-force NdFeB-based magnetic tweezers device optimized for microrheology experiments Rev. Sci. Instrum. 83, 053905 (2012);Dry etch behavior of Fe in inductively coupled chlorine-based plasma at elevated temperatures has been investigated. Etch rates up to 300 nm/min at 190°C were achieved, with good selectivity towards SiO 2 and Al 2 O 3 masks. Etching did no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2008
2008
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…They observed a maximum etch rate at 50% Cl 2 , and a strong increase in etch rate between 0 and 25% Cl 2 . These results, in association with Andriesse's findings [36], show that Fe can be sensitive to chemical etching with neutral Cl, with a dependence on the substrate temperature. FeCl 3 has a vaporization temperature of 316 • C at atmospheric pressure [38].…”
Section: Literature Overviewsupporting
confidence: 86%
See 1 more Smart Citation
“…They observed a maximum etch rate at 50% Cl 2 , and a strong increase in etch rate between 0 and 25% Cl 2 . These results, in association with Andriesse's findings [36], show that Fe can be sensitive to chemical etching with neutral Cl, with a dependence on the substrate temperature. FeCl 3 has a vaporization temperature of 316 • C at atmospheric pressure [38].…”
Section: Literature Overviewsupporting
confidence: 86%
“…They measured an etch rate of 100-150 nm/min for N i and F e in some conditions. Andriesse et al [37] observed a strong increase of F e etch rate when the substrate temperature increases from 70 to 200 o C, while the etch rate slowly increases with bias from 0 to -75 V . XPS (X-Ray Photoelectron Spectroscopy) analyses revealed the presence of F e − Cl bonds, proving the chemical adsorption of Cl on the surface etched by Cl 2 /BCl 3 .…”
Section: Literature Overviewmentioning
confidence: 99%